2007
DOI: 10.1002/syn.20368
|View full text |Cite
|
Sign up to set email alerts
|

Consistent with dopamine supersensitivity, RGS9 expression is diminished in the amphetamine‐treated animal model of schizophrenia and in postmortem schizophrenia brain

Abstract: It is known that RGS9-2 gene knockout mice show supersensitivity to DA and have a marked elevation in the proportion of DA D2 receptors in the high-affinity state for DA (D2(High) receptors). As this is a similar profile to that observed in the CNS from subjects with schizophrenia, we examined whether postmortem CNS tissue from subjects with the disorder and brain striata from an animal model of psychosis or schizophrenia (the amphetamine-sensitized rat) had altered levels of RGS9-2. The mRNA for RGS9-2 in 29 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 16 publications
8
50
0
1
Order By: Relevance
“…In the current study, we found a significant increase in the midbrain RGS2 and RGS4 mRNA levels 18 h following 5 days of AMPH self-administration. Reports on RGS2 mRNA levels following non-contingent AMPH treatment have not been consistent with no change (Burchett et al, 1998) and an increase (Seeman et al, 2007) owing to different lengths of AMPH treatment and withdrawal. These data suggest that AMPH modulates RGS2 mRNA levels in a brain region-dependent manner.…”
Section: Amph Self-administration Selectively Promoted Membrane Transmentioning
confidence: 93%
“…In the current study, we found a significant increase in the midbrain RGS2 and RGS4 mRNA levels 18 h following 5 days of AMPH self-administration. Reports on RGS2 mRNA levels following non-contingent AMPH treatment have not been consistent with no change (Burchett et al, 1998) and an increase (Seeman et al, 2007) owing to different lengths of AMPH treatment and withdrawal. These data suggest that AMPH modulates RGS2 mRNA levels in a brain region-dependent manner.…”
Section: Amph Self-administration Selectively Promoted Membrane Transmentioning
confidence: 93%
“…Dopaminergic pathways play a critical role in diseases such as Parkinson's disease (nigrostriatal system), schizophrenia, and addiction (mesolimbic and mesocortical system) (Li & Ma 2013). In schizophrenia, cortical D2Rs may be hypersensitive to dopamine (Seeman et al 2005(Seeman et al , 2007 or present in increased amounts in some regions. The prokineticin system is related to several physiological and pathological conditions (MaldonadoPerez et al 2007, Negri et al 2007, Zhou et al 2012.…”
Section: R68 Reviewmentioning
confidence: 99%
“…Similarly, GWAS studies have also indicated that another SNP in RGS6 (rs2332700) is significantly associated with schizophrenia (25). The possible significance of RGS6's role in schizophrenia is further supported by preliminary studies which also suggest that RGS7 and RGS9 may be differentially expressed in patients with schizophrenia (86,87) and may modulate brain responses to psychostimulants and antipsychotics (49,(88)(89)(90)(91)(92)(93). Finally, not only is there substantial evidence detailing the critical role of various R7 family members in proper vision (94-97) but a splice acceptor variant of RGS6 (c.1369-1G>C) has also been positively associated with the familial inheritance of congenital cataracts (26).…”
Section: Alzheimer's Disease Schizophrenia and Eye-related Disordersmentioning
confidence: 84%